The Urgency of Limiting The Utilization of Consumer IP Addresses by Companies as Personal Data Objects in The Study of Positive Law in Indonesia - Firdhausya, Mahima Umaela; Aflah, Muhammad Hilmi Naufal; Tussaleha, Anisa; Mukminto, Eko; Putra, Tegar Islami (Universitas Negeri Semarang, 2024)
The era of the digital revolution moves very quickly following the times with various consequences in it. The issuance of Law Number 27 of 2022 concerning Personal Data Protection is one of the government's responses to the times, especially to see the importance of paying attention to personal data management. In this regulation, it provides the nomenclature of IP Address as one of the types of personal data combined as explained in Article 4 paragraph (3). This article aims to analyze how the form of consumer IP Address utilization by e-commerce service provider companies in Indonesia based on applicable positive law. The method used in writing this article is a qualitative method using a conceptual approach. The findings of this research are the known forms of consumer IP Address utilization by companies are to analyze consumer behavior on application services, conduct experience personalization, perform bandwidth management, and manage transaction security. The urgency of limiting the utilization of consumer IP addresses by companies as personal data objects is a form of privacy protection, providing data security, and complying with applicable laws in Indonesia.